Seasonal movements of immature Kemp's ridley sea turtles (Lepidochelys kempii) in the northern gulf of Mexico. Issue 1 (23rd May 2016) - Coleman, Andrew T.; Pitchford, Jonathan L.; Bailey, Helen; Solangi, Moby
Abstract: Seasonal movements and core habitat areas of immature Kemp's ridley sea turtles ( Lepidochelys kempii ) in the northern Gulf of Mexico were tracked via satellite telemetry. Tagged turtles were incidentally captured by recreational fishermen and rehabilitated at the Institute for Marine Mammal Studies in Gulfport, Mississippi. The average size of the core habitat areas (50% KDE (kernel density estimation)) was 1660.2 km 2 ± 3438.2 SD. Turtles displayed strong intra‐ and inter‐annual site fidelity to the Mississippi Sound during the spring, summer, and autumn months. During the winter months, most turtles, probably influenced by water temperatures, migrated to nearshore waters of Louisiana on either side of the Mississippi River Delta. However, other migration strategies were also observed. Overall, these data indicate that the Mississippi Sound is an important developmental habitat for this critically endangered species. In addition, their wintering grounds in Louisiana are utilized by adult Kemp's ridleys and other sea turtle species as foraging grounds and migratory corridors. The high use of these areas by sea turtle populations increases the potential for negative impacts from anthropogenic disturbances (e.g. shrimp trawling, oil production, hypoxia) that occur there. Copyright © 2016 John Wiley & Sons, Ltd.